Improvement of dissolution rate and aqueous solubility of nitrazepam by solid dispersion technique - Singh S.; Sathali A.A.H.; Jayaswal S.B. (My University, 2025)
The aqueous solubility and dissolution rate of nitrazepam were increased using solid dispersion technique. The solvent fusion and coprecipitation methods were employed (with different solvents) to prepare the solid dispersion with polyethylene glycol (PEG) and polyvinyl pyrrolidone (PVP) polymers of different molecular weights, The solid dispersions were evaluated for drug content and dissolution rate. The dissolution rates were affected by the solvent used, molecular weight of the polymer, drug: polymer ratio and the technique employed. The solid dispersion with PVP 44000, solvent chloroform and drug: polymer ratio 1: 19 (Batch L1) displayed maximum aqueous solubility and the best dissolution rate. Studies showed a change in the physical state of the drug from crystalline to amorphous form in solid dispersion. The tablet prepared with Batch L1 showed drug released in nearly zero-order fashion in comparison to the marketed product. The stability studies carried out at three different temperatures showed no change in the drug content of the prepared tablets.